Progress and perspectives of platinum nanozyme in cancer therapy - Wang, Xi; He, Xueting; Liu, Chaofan; Zhao, Weiheng; Yuan, Xianglin; Li, Rui (Frontiers in Chemistry, 2022)
Malignant tumors, one of the worst-case scenarios within human health problems, are now posing an increasing threat to the well-being of the global population. At present, the treatment of malignant tumors mainly includes surgery, radiotherapy, chemotherapy, immunotherapy, etc. Radiotherapy and chemotherapy are often applied to inoperable tumors, and some other tumors after surgery as important adjuvant therapies. Nonetheless, both radiotherapy and chemotherapy have a series of side effects, such as radiation-induced lung injury, and chemotherapy y-induced bone marrow suppression. In addition, the positioning accuracy of radiotherapy and chemotherapy is not assured and satisfactory, and the possibility of tumor cells not being sensitive to radiation and chemotherapy drugs is also problematic. Nanozymes are nanomaterials that display natural enzyme activities, and their applications to tumor therapy have made great progress recently. The most studied one, platinum-based nanozyme, has been shown to possess a significant correlation with radiotherapy sensitization of tumors as well as photodynamic therapy. However, there are still several issues that limited the usage of platinum-based nanozymes in vivo. And thus in this review, we briefly summarize the representative studies regarding platinum-based nanozymes, and especially emphasize on the current challenges and the directions of future development for platinum-based nanozyme therapy.